2002
DOI: 10.1016/s0022-5347(05)65178-6
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Unenhanced Helical Computerized Tomography For The Evaluation Of Acute Flank Pain

Abstract: Even with the significantly decreased radiation exposure of the low dose protocol unenhanced helical CT is still an excellent and rapid diagnostic tool for evaluating acute flank pain with lower radiation exposure than excretory urography (HE 1.3 to 2.3 mSv.) at our departments. Only in obese patients with a body mass index of greater than 31 kg./m.2 is conventional unenhanced helical CT with higher radiation exposure recommended to achieve adequate image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(43 citation statements)
references
References 17 publications
0
42
0
1
Order By: Relevance
“…Previous studies have shown that reduced-dose CT studies are accurate for the detection of renal stones (13)(14)(15)(16)(17)(18)(19). A meta-analysis (20) of reduced-dose CT for renal colic (with effective dose less than 3 mSv) yielded a pooled sensitivity and specificity of 0.97 and 0.95, respectively, compared with conventional CT.…”
mentioning
confidence: 98%
“…Previous studies have shown that reduced-dose CT studies are accurate for the detection of renal stones (13)(14)(15)(16)(17)(18)(19). A meta-analysis (20) of reduced-dose CT for renal colic (with effective dose less than 3 mSv) yielded a pooled sensitivity and specificity of 0.97 and 0.95, respectively, compared with conventional CT.…”
mentioning
confidence: 98%
“…Implementation of radiation dose reduction strategies may be a more attainable goal that can be more consistently applied. Data from both the adult 19-23 and pediatric 24 literature demonstrate that CT dose reductions of >50% are attainable without sacrificing diagnostic quality for the vast majority of patients with SU. Ultimately, the decision regarding whether to apply a staged ultrasound +/- CT, a CT dose-reduction protocol, or both lies with the individual hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors 5,8,16,17 used NCHCT scanning with a collimation of 5 mm to evaluate acute flank pain. The use of 1 mm collimation is clinically impractical in the routine evaluation of acute flank pain.…”
Section: Discussionmentioning
confidence: 99%